Exploring the Role of Educational Technology in Shaping University Students’ Learning Interest - Tri Endar Yogi Setiadi Saputra; Yusni Yusni; Irsyam Surahim; Syachrir Syamsuddin (FOSTER: Journal of English Language Teaching, 2025)
This study explores the role of educational technology in shaping university students’ learning interest. The research problem focuses on how educational technology contributes to shaping students’ learning interest at the University of Mega Buana Palopo. The objective of this study is to examine the role of educational technology in influencing university students’ learning interest at the University of Mega Buana Palopo. This research employed a qualitative research design. The researcher applied a purposive sampling technique to collect the data, with special consideration given to students who had high average scores in class, particularly in English. Data were collected through interviews, observations, and documentation. Based on the findings, the researcher concluded that educational technology plays a significant role in the learning process, particularly in enhancing students’ learning interest. The results indicate that the use of educational technology has a very positive impact on the learning process by providing access to a wide range of learning resources and making learning more interactive. In addition, educational technology makes it easier for students to access information and complete assignments. Technology also influences the learning process by offering abundant information and enhancing digital literacy, which ultimately makes learning more engaging for students.